Genome-Based Characterization of Plant-Associated Rhodococcus qingshengii RL1 Reveals Stress Tolerance and Plant–Microbe Interaction Traits - Kuhl, Theresa; Chowdhury, Soumitra Paul; Uhl, Jenny; Rothballer, Michael (Frontiers in Microbiology, 2021)
Stress tolerant, plant-associated bacteria can play an important role in maintaining a functional plant microbiome and protecting plants against various (a)biotic stresses. Members of the stress tolerant genus Rhodococcus are frequently found in the plant microbiome. Rhodococcus qingshengii RL1 was isolated from Eruca sativa and the complete genome was sequenced, annotated and analyzed using different bioinformatic tools. A special focus was laid on functional analyses of stress tolerance and interactions with plants. The genome annotation of RL1 indicated that it contains a repertoire of genes which could enable it to survive under different abiotic stress conditions for e.g. elevated mercury concentrations, to interact with plants via root colonization, to produce phytohormones and siderophores, to fix nitrogen and to interact with bacterial signaling via a LuxR-solo and quorum quenching. Based on the identified genes, functional analyses were performed in vitro with RL1 under different growth conditions. The R. qingshengii type strain djl6 and a closely related Rhodococcus erythropolis BG43 were included in the experiments to find common and distinct traits between the strains. Genome based phylogenetic analysis of 15 available and complete R. erythropolis and R. qingshengii genome sequences revealed a separation of the R. erythropolis clade in two subgroups. First one harbors only R. erythropolis strains including the R. erythropolis type strain. The second group consisted of the R. qingshengii type strain and a mix of R. qingshengii and R. erythropolis strains indicating that some strains of the second group should be considered for taxonomic re-assignment. However, BG43 was clearly identified as R. erythropolis and RL1 clearly as R. qingshengii and the strains had most tested traits in common, indicating a close functional overlap of traits between the two species.